Meaning-theoretical conditions and Verification: a defense of Dummett against Alfred Tarski - Ribeiro Vollet, Lucas (2024)
In the upcoming article, we will explore a critique of Dummett's towards Tarski that has often been overlooked or not fully appreciated. Dummett's verificationist anti-realism serves as the foundation for the critique. According to this author, a theory of meaning for a particular language—which are found in a theory of harmony—determine the circumstances in which the meaning of a sentence of the language can be theorized, or presented in a strategic and non-defeating theoretical depiction of its possible assertion. These prerequisites create a mediating bridge between the statement of a sentence and its effects, defining the circumstances in which the incompatibility of "p" and "not-p" can be considered and projected. Tarski is criticized for his formal and material semantic theory of truth, which hides or masks the epistemic circumstances by presenting them in a straightforward and codified manner in inductive principles.